The Fundamentals of a Two-Stage Approach to Systematic Earthquake Prediction - Gitis Valeriy; Derendyaev Alexander (Russian Journal of Earth Sciences)
A systematic earthquake prediction is performed regularly at fixed intervals within a preselected seismically homogeneous zone. The result of each prediction iteration is a map highlighting the alarm zones, where the epicenters of target earthquakes are expected. The proposed methodology introduces the following innovations: 1 – A prediction is considered successful if all epicenters of the target earthquakes during the forecast interval fall within the alarm zone. 2 – The methodology optimizes both the probability of successfully detecting earthquake epicenters across a series of forecasts and the success rate of predictions in each individual iteration. 3 – The methodology enables the estimation of the probability of success for the next forecast interval. Examples of the method's application are demonstrated for predicting earthquakes in Kamchatka, California, and the island region of Japan.